Self-(In)compatibility Systems: Target Traits for Crop-Production, Plant Breeding, and Biotechnology - Muñoz-Sanz, Juan Vicente; Zuriaga, Elena; Cruz-García, Felipe; McClure, Bruce; Romero, Carlos (Frontiers in Plant Science, 2020)
Self-incompatibility (SI) mechanisms prevent self-fertilization in flowering plants based on specific discrimination between self- and non-self pollen. Since this trait promotes outcrossing and avoids inbreeding it is a widespread mechanism of controlling sexual plant reproduction. Growers and breeders have effectively exploited SI as a tool for manipulating domesticated crops for thousands of years. However, only within the past thirty years have studies begun to elucidate the underlying molecular features of SI. The specific S-determinants and some modifier factors controlling SI have been identified in the sporophytic system exhibited by Brassica species and in the two very distinct gametophytic systems present in Papaveraceae on one side and in Solanaceae, Rosaceae, and Plantaginaceae on the other. Molecular level studies have enabled SI to SC transitions (and vice versa) to be intentionally manipulated using marker assisted breeding and targeted approaches based on transgene integration, silencing, and more recently CRISPR knock-out of SI-related factors. These scientific advances have, in turn, provided a solid basis to implement new crop production and plant breeding practices. Applications of self-(in)compatibility include widely differing objectives such as crop yield and quality improvement, marker-assisted breeding through SI genotyping, and development of hybrids for overcoming intra- and interspecific reproductive barriers. Here, we review scientific progress as well as patented applications of SI, and also highlight future prospects including further elucidation of SI systems, deepening our understanding of SI-environment relationships, and new perspectives on plant self/non-self recognition.